Resource allocation for minimal downlink delay in two-way OFDM relaying with network coding - Ke Xiong; Pingyi Fan; Ben Letaief, Khaled; Su Yi; Ming Lei (2012 IEEE International Conference on Communications (ICC), 2012)
This paper investigates the resource allocation problem to minimize the downlink transmission delay under power constraints for two-way relay transmission using network coding over OFDM channels, where two sources with unbalanced traffic exchange their information via a relay node with network coding deployed. Since the explicit solution to this optimization problem is hard to obtain and with extremely high computation complexity even for numerical solution, we propose low-complexity suboptimal algorithms for the problem, where subcarrier assignment is carried out by assuming an equal power distribution at first and then optimal power allocation is executed to minimize the transmission delay. By simulations, the proposed resource allocation scheme is shown to achieve less than 1.01 times the optimal delay and outperform the strategies without network coding in overwhelming majority cases.